"Breaking the cycle": Black adolescents' experiences of being stereotyped during identity development. Issue 2 (24th April 2017) - Lombaard, Nelani; Naudé, Luzelle
Abstract : This study explored the experience of being stereotyped in a group of black South African adolescents. Participants were 73 black adolescents between the ages of 13 and 17 (females = 43.8%, majority ethnicity Setswana = 43, 8%). The adolescents participated in focus group discussions on their experience of ethnicity-based stereotyping by others. The data were thematically analysed. The adolescents reported to experience identity compromising stereotyping related to gender roles, sexual orientation, race, and language. Gender-based stereotypes predominantly related to education and career opportunities; with females perceived to be less educated and to have poorer career prospects than male peers. Racial stereotyping was linked to discrimination and xenophobia; and being different was distrusted. Individuals who choose to speak English were stereotyped as culturally superior to those who speak indigenous languages. The adolescents reported to cope with stereotyping by taking actions to contradict stereotypical expectations (find common goals, increase intergroup cooperation, and appreciate difference and uniqueness in people). Stereotype vulnerability in adolescent groups was confirmed, as well as that stereotypes can shape identity outcomes. In addition to this, the importance of intergroup contact to eradicate stereotypes was reiterated.